Accelerated Wound Healing in Diabetic Rat by miRNA-185-5p and Its Anti-Inflammatory Activity - Wang KX; Zhao LL; Zheng LT; Meng LB; Jin L; Zhang LJ; Kong FL; Liang F (Diabetes, Metabolic Syndrome and Obesity, 2023)
Kui-Xiang Wang,1 Li-Li Zhao,1 Ling-Tao Zheng,2 Li-Bin Meng,1 Liang Jin,3 Long-Jun Zhang,4 Fan-Lei Kong,1 Fang Liang2 1Department of Orthopaedics, Xingtai People’s Hospital of Hebei Medical University, Xingtai, Hebei Province, 054000, People’s Republic of China; 2Department of Endocrinology, Xingtai People’s Hospital of Hebei Medical University, Xingtai, Hebei Province, 054000, People’s Republic of China; 3Department of Hand and Foot Surgery, Xingtai People’s Hospital of Hebei Medical University, Xingtai, Hebei Province, 054000, People’s Republic of China; 4Department of Plastic and Burn, Xingtai People’s Hospital of Hebei Medical University, Xingtai, Hebei Province, 054000, People’s Republic of ChinaCorrespondence: Fang Liang, Email 1628960867@qq.comAim: Addressing both inflammation and epithelialization during the treatment of diabetic foot ulcers is an important step, but current treatment options are limited. MiRNA has important prospects in the treatment of diabetic foot refractory wound ulcers. Previous studies have reported that miR-185-5p reduces hepatic glycogen production and fasting blood glucose levels. We herein hypothesized that miR-185-5p might play an important role in the field of diabetic foot wounds.Materials and Methods: MiR-185-5p in skin tissue samples from patients with diabetic ulcers and diabetic rats were measured using quantitative real-time PCR (qRT-PCR). The streptozotocin-induced diabetes rat model (male Sprague-Dawley rats) for diabetic wound healing was conducted. The therapeutic potential was observed by subcutaneous injection of miR-185-5p mimic into diabetic rat wounds. The anti-inflammation roles of miR-185-5p on human dermal fibroblast cells were analyzed.Results: We found that miR-185-5p is significantly downregulated in diabetic skin (people with DFU and diabetic rats) compared to controls. Further, in vitro upregulation of miR-185-5p decreased the inflammatory factors (IL-6, TNF-α) and intercellular adhesion molecule 1 (ICAM-1) of human skin fibroblasts under advanced glycation end products (AGEs). Meanwhile, the increase of miR-185-5p promoted cell migration. Our results also confirmed that the topical increase of miR-185-5p decreases diabetic wound p-nuclear factor-κB (p-NF-κB), ICAM-1, IL-6, TNF-α, and CD68 expression in diabetic wounds. MiR-185-5p overexpression boosted re-epithelization and expedited wound closure of diabetic rats.Conclusion: MiR-185-5p accelerated wound healing of diabetic rats, reepithelization, and inhibited the inflammation of diabetic wounds in the healing process, a potentially new and valid treatment for refractory diabetic foot ulcers.Keywords: diabetes, miRNA, wound healing, inflammation